Health Information-Seeking Behavior of Menopausal Women: An Online Survey of Iranian Menopausal Women - Masoomeh Latifi; Nader Alishan Karami; Sepideh Miraj; Leili Allahbakhshian; Forough Rahimi; Afsaneh Karbasi (Iranian Journal of Nursing and Midwifery Research)
Background: Understanding the health information behavior of menopausal women can be effective on their health awareness and improving self-care and preventive health practices. This study aimed to gain deeper insights into the health information-seeking behavior of Iranian menopausal women. Materials and Methods: This descriptive–analytical cross-sectional study was conducted in 2023. Data were collected over 2 months, from June 15 to August 15, 2023. The participants were Iranian women aged 50 years and older at the time of the survey. An online questionnaire was developed and distributed through social media to assess the health information-seeking behavior of menopausal women. A total of 4,608 women, selected through cluster sampling, completed the questionnaire. The data were analyzed using SPSS-23 software using the Chi-square test. Results: The primary information needs of women during menopause were related to cancer, other diseases, and diagnostic methods. In addition, social networks and friends were the most commonly used information sources among menopausal women. The main barriers to accessing information were the lack of knowledge about information sources, difficulties in obtaining accurate and reliable information, and insufficient information across various sources. Conclusions: The findings of this study indicated that women required various types of information, particularly regarding cancers, clinical symptoms of menopause, and nonhormonal treatments. Given the increasing use of social networks, training can be conducted through these platforms and further efforts are necessary to provide more reliable and comprehensive information via these media.